Thermodynamic Parameters Of Solutions Of Sildenafil Citrate In Some Organic Solvents At Different Temperatures - Baluja, S.; Bhesaniya, K. (University of Eloued جامعة الوادي, 2014)
The solubility of Sildenafilcitrate in someorganic solvents; hexane, toluene,1-butanol and 1,2 dichloroethanehas been determined using gravimetric method over different temperature range (298.15 K to 328.15 K) at one atmospheric pressure. The modified Apelblat and Buchowski-Ksiazczak λh equations were used to correlate the experimental solubility data.Further, various thermodynamic parameters have been evaluated from these solubility data.
Articale in Journal of fundamental and Applied Sciences Vol. 06 N. 01
Keywords: Solubility, Organic solvents, Sildenafil citrate, Thermodynamic parameters